Terrorism and Tourism : The Stock Market Reaction - Chua, Hui Gee (2005)
The tourism sector has inadvertently been seen as the logical companion of terrorism. With terrorism being associated with negative abnormal returns in the capital markets, the linkage of tourism with terrorism implicates greater negative association. This research examines the validity of the association of four terrorist attacks; the 9/11, Bali Bombing, Marriot hotel bombing, and the 7/7 London Bombings on four respectively selected groups of hotels and hotel managements stocks. The standard event study methodology is used with Carrado Ranking Test where necessary. The overall results show mixed reaction. 9/11 is found to be negatively associated with abnormal return. Bali bombings are not negatively associated. The Marriot hotel bombings and 7/7 London Bombings are associated with negative abnormal returns. The hypothesis that abnormal return is associated negatively with terrorism cannot be fully substantiated.